If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 89 = 3x + 5x + -7 Reorder the terms: 89 = -7 + 3x + 5x Combine like terms: 3x + 5x = 8x 89 = -7 + 8x Solving 89 = -7 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 89 + -8x = -7 + 8x + -8x Combine like terms: 8x + -8x = 0 89 + -8x = -7 + 0 89 + -8x = -7 Add '-89' to each side of the equation. 89 + -89 + -8x = -7 + -89 Combine like terms: 89 + -89 = 0 0 + -8x = -7 + -89 -8x = -7 + -89 Combine like terms: -7 + -89 = -96 -8x = -96 Divide each side by '-8'. x = 12 Simplifying x = 12
| -2.4x+9=8 | | f(x)=2x^8-3x | | 3(x+4x)+3x= | | 1.2x+4=9 | | 8w^2-4w-4=0 | | (3x+7)(6x+3)=0 | | 10x+15=68-8x | | .25n(6n-3)=4n+1 | | A+3a-5=-78 | | 2p+(-3)(1-p)=(-2)p+1(1-p) | | (D/7)-1=8 | | 6b^2=48 | | 5g-7.8=62.7 | | 2p^2-6p-9=0 | | 2x+7x+9=0 | | 5z^2-9z-7=0 | | 24x^2+100x+100=0 | | 7x-4=57 | | y=0.05x^2-x+480 | | -6j+18=3j-3 | | 8m^2-6=0 | | 17+x=130 | | (2x-7x^2+3x^3)=60 | | -3x-6=-2x-14 | | 13x+3=27-3x | | -x-2=15x | | .5x+1.5= | | 2x+6=134 | | x-22+3x=-29-3x-33 | | -64x^2+56x-12=0 | | 20(0.5882352941)+(-20)(1-0.5882352941)=x | | -7c+-2d= |